2017
DOI: 10.1021/acs.joc.7b02403
|View full text |Cite
|
Sign up to set email alerts
|

Further Investigation of the Intermolecular Diels–Alder Cycloaddition for the Synthesis of Bicyclo[2.2.2]diazaoctane Alkaloids

Abstract: The convergent synthesis of bicyclo[2.2.2]diazaoctane structures using an intermolecular Diels-Alder cycloaddition between a pyrazinone and commercially available fumarate or maleate precursors is reported. High reactivity and stereoselection is observed with both dienophile substrates. Structure validation was achieved by conversion of cycloadducts into known [2.2.2]diazabicyclic compounds or into crystalline derivatives suitable for X-ray analysis. The cycloadduct derived from reaction of pyrazinone and male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…We found that for the Diels–Alder cyclization of (+)-dehydrodeoxybrevianamide E (9) Williams' conditions of methanolic KOH gave a better result than our aqueous LiOH conditions ( Scheme 9 ). 12 Racemic syn - and anti -configured bicyclo[2.2.2]diazaoctane products, 14 and 6, were isolated in 53% yield with modest syn -diastereoselectivity (d.r. 57 : 43).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that for the Diels–Alder cyclization of (+)-dehydrodeoxybrevianamide E (9) Williams' conditions of methanolic KOH gave a better result than our aqueous LiOH conditions ( Scheme 9 ). 12 Racemic syn - and anti -configured bicyclo[2.2.2]diazaoctane products, 14 and 6, were isolated in 53% yield with modest syn -diastereoselectivity (d.r. 57 : 43).…”
Section: Resultsmentioning
confidence: 99%
“…12 Thus, although this strategy hasn't provided a route to brevianamide A ( 1 ), several syntheses of brevianamide B ( 2 ) have been achieved that proceed via intermediate 6 , or protected analogues thereof (see structures in Scheme 1b). 12 Most notably, Williams and co-workers have achieved four syntheses of brevianamide B ( 2 ). In 1988, they reported the first total synthesis of ent -brevianamide B ( ent - 2 ) using a late-stage cationic cyclization, which resulted in an 18-step total synthesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Furthermore, despite five decades of research, no chemical synthesis of brevianamide A (1) has been achieved, yet several syntheses of the minor diastereomer, brevianamide B (2), have been reported (see SI for a full summary). [17][18][19][20][21][22][23][24][25] Despite the similar structures of the two natural products, none of these strategies have been successfully applied to the synthesis of brevianamide A (1) due to insurmountable issues of stereoselectivity. Following decades of detailed chemical and biochemical studies, the biosynthetic origins of (+)-brevianamide A (1) and B (2) still remain largely unknown.…”
mentioning
confidence: 99%